Behaviour of steel-reinforced concrete columns under combined torsion based on ABAQUS FEA. (15th April 2020) - Cao, Xiaoluo; Wu, Linmei; Li, Zhenming
Highlights: Initial torsion stiffness increases with increasing concrete strength and decreases with increasing shear-span ratio. Ductility was reduced torsion-bending ratio increased and the energy dissipation capacity decreased. Influence order of parameters on the ultimate torsion is: concrete strength, shear/span, steel ratio, torsion/bending, stirrup ratio, longitudinal reinforcement ratio and axial load ratio. Influence order of parameters on the ductility coefficient is: steel ratio, shear/span, concrete strength, axial load ratio, stirrup ratio, torsion-bending ratio and longitudinal reinforcement ratio. Abstract: A computational model for studying the mechanical performance of steel-concrete columns under combined torsion is established via ABAQUS. The model is validated by experimental results. Through numerical simulations, the influence of the axial load ratio, torsion-bending ratio, concrete strength, steel ratio, longitudinal reinforcement ratio, stirrup ratio, and shear-span ratio on the torsional behaviour of steel-concrete columns is comprehensively investigated. The initial torsion stiffness and ultimate torsion strength of the column increase with increasing concrete strength and decreasing shear-span ratio. The parameters in descending order of influence on the ultimate torsion strength are steel ratio, torsion-bending ratio, stirrup ratio, longitudinal reinforcement ratio, and axial load ratio. Furthermore, the seven parameters in descending order of influence on the ductility coefficient are the steel ratio, shear-span ratio, concrete strength, axial load ratio, stirrup ratio, torsion-bending ratio and longitudinal reinforcement ratio.